Customer Reviews And Price Influence On Repurchase Intention of Kebaya In Tiktok Shop - Sinatriya Prawatya Respati (CITACONOMIA : Economic and Business Studies, 2023)
Repurchase intention serves as a crucial indicator for assessing consumer loyalty to a brand or product. The purpose of this study is to examine the impact of social media, online customer reviews, and price on consumers’ repurchase intention toward kebaya products available on the TikTok Shop platform, with particular emphasis on the local brand Outfit Nusant. This research applies a quantitative method, utilizing non-probability sampling through purposive sampling. The sample includes 385 respondents who have previously purchased Outfit Nusant products via TikTok Shop. Data were obtained using questionnaires and analyzed with SPSS version 16. Findings reveal that social media, online customer reviews, and price exert a positive and significant influence on consumers’ repurchase intention for kebaya products in TikTok Shop Outfit Nusant.